If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + -1(3x + 2) = 0 Reorder the terms: 26 + -1(2 + 3x) = 0 26 + (2 * -1 + 3x * -1) = 0 26 + (-2 + -3x) = 0 Combine like terms: 26 + -2 = 24 24 + -3x = 0 Solving 24 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -3x = 0 + -24 Combine like terms: 24 + -24 = 0 0 + -3x = 0 + -24 -3x = 0 + -24 Combine like terms: 0 + -24 = -24 -3x = -24 Divide each side by '-3'. x = 8 Simplifying x = 8
| 5x-17=2x+10 | | 22=11k | | 14-x=48 | | 2c-3+9d+7-6d= | | x+(x-26)=180 | | 1h+1+2h+1=6h+6-1h+2 | | 5+9y=5y+5 | | x(y-3)=40 | | 5x+4=23 | | 2c/11=(c-3)/4 | | 8=-2x+4-2 | | 2x-1=24.5 | | 5+x=5y+5 | | x^2-10x+10= | | 2c/11=c-3/4 | | 6+3x=11-2x | | 256=6x-4(-4x-20) | | 9y+5=5y | | k-76.98=43.56 | | x=9y | | 20x+15-5=180 | | 65+x+x-5=180 | | 3y-9+y+45=5y+40-3y | | 9x+5=5y+5 | | -1=6a-1+6a | | 0.6x-3.9=0.6 | | -8k+26=-8k | | -.5(16-2h)=11 | | 2y+19+y=7y-9 | | 3(x-5)+1=(1/4)(2x-8) | | 11+(7+n)=24 | | -3y+8=-12x |